MEDICATION IDENTIFICATION SYSTEM - Pederson, Christopher G; O'Brien, Nada A (2023)
A medication identification system for identifying medication using a transflective (transmission and reflection - based) spectrometer and performing an analysis of the light spectrum after having passed twice the medication to be identified. Medication probe holder coated with reflective material.